Penerapan Pendidikan Karakter dan Pancasila Melalui Pelajaran PPKn di SMA N 4 Kota Jayapura - Ode Jamal; Holiek Kobak (Jurnal Pengabdian Masyarakat Waradin, 2024)
Character education and Pancasila are important aspects in shaping students' personalities in Indonesia. This study aims to explore the application of character education and Pancasila values ​​through Pancasila and Citizenship Education (PPKN) learning at SMA N 4 Jayapura City. The method used is a qualitative approach with data collection through interviews, observations, and documentation. The results of the study indicate that the application of character education and Pancasila in this school has been running well, although there are still obstacles in its implementation. This study is expected to contribute to the development of character education in Indonesia.